DEGRADASI KADAR FORMALIN PADA DAGING AYAM BROILER (Gallus domesticus) BERFORMALIN OLEH SARI BUAH CERMAI (Phyllanthus acidus L.) - N.A. Elhany; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2014)
An experimental research has been carried out to investigate the effect of fruit juice cermai (Phyllantusacidus.L)concentration on reduce of formaldehyde levels andtendernessin broiler chicken (Gallus domesticus) of formaldehyde meat. This research have used 20 chest of broiler meat weighing 100 g respectively. Meat have been soaked in 10% formalin solution for 1 hour. Meat have randomly divided into 5 treatments and each soaked in fruit juicecermai 0%, 15%, 30%, 45% and 60% for 30 minute. Formaldehyde levelsin meat have analized by spectrophotometer at 415 nm and tenderness of meat have analized by phenetrometer. The results showed soaking treatment with a fruit juice cermai (Phyllantusacidus.L) 15%, 30%, 45% and 60% have a significant effect (P <0.05) to reduce of formaldehyde levels and meat tenderness in broiler meat formalin. The results of this research it can concluded the administration of fruit juice cermai (Phyllantusacidus.L) 60% can reduce formaldehyde levels high of 92.13% and a yield of broiler meat tenderness formaldehyde maximum of 490.25 mm/ 100g /10 seconds. Keywords : Cermai (Phyllanthus Acidus L.), degradation of formaldehyde, tenderness, broiler chickens